Pergeseran Pola Kepemimpinan Kiai dalam Mengembangkan Lembaga Pesantren - Mahfudz Sidiq (STAIFAS-Press, 2020)
The development and sustainability of Islamic Boarding School are strongly influenced by the regeneration of the leadership of kiai as a successor of the vision and mission, depending upon their disciplines. Regeneration of the leadership of kiai often occurs on the basis of lineage to maintain and respond the developmental and institutional dynamics in the boarding school. The research is intended to analyze and discover the leadership patterns of kiai, the shifting patterns of the leadership, and the impact of the shift towards the development of the institutions. This study is phenomenological. The data collection techniques employed were observation, in-depth interviews, and documentation. The data analysis procedures were data reduction, data display, and conclusion. Tringualation was used to check the data validity, credibility, transferability, dependability, and confirmability.The findings of the research reveal the following results. Firstly, the pattern of the leadership of kiai is preserving and maintaining lineage or dzurriyyah (leader is born). The characteristics of the leadership of kiai are paternalistic, charismatic, pseudo-democratic, and transcendent-transformative. Secondly, the shifting patterns of the leadership of kiai are maintaining direct dzurriyah, direct and closest dzurriyyah, and indirect and closest dzurriyyah. The patterns are based on the following principles: a) capable to maintain knowledge and the characteristics of the boarding school, b) able to maintain the values of the ​​boarding schools and families (dzurriyyah), c) able to maintain the values ​​and patterns of leadership characteristics which are paternalistic, charismatic, pseudo-democratic, and transcendent-transformative, and d) finally, able to maintain the institutional characteristics of the boarding schools which are salafiyah, salafiyah-khalafiyah, and khalafiyah. Thirdly, the impacts of the leadership shift of kiai are as follows. a) the leadership pattern is more open and accepts value changes. b) Diversity of institutional models occurs from salafiyah, salafiyah-khalafiyah, and khalafiyah. c) the models of institutional buildings are from wood and bamboo to modern buildings. d) the quality of human resources is in the forms of expertises religious knowledge and science. e) the management of santri is from traditional to classical management models, and f) the outputs or graduates involve in the works for the religious instution and community services in his environment.